The effectiveness of marketing tools in student admission in higher education institutes in Malaysia - Abd Aziz, Mohamad Azlan (2012)
In Malaysia, there are lots of Higher education's institutions (HEI) operated and this created a stiff competition among the institution to attract student's admission into their HEI. Thus, this study is to find the inter relation in between the marketing mix concept with perception of students when selecting the HEI to pursue their study. The marketing mix (Marketing Tools) strategies developed earlier by Edmund J. McCarthy in 1960 explained about the 4 elements of marketing concept (4Ps) which in this study, the idea expanded into 7 elements that are product (course offered by HEI), Price (the cost associated with study at HEI), Place (location of HEI), Promotion, Peoples (the academics and staff of HEI), Process (administration of HEI) and Physical presence (facilities of HEI). All of these marketing tools were studied in order to find the most effective elements that can attract student's enrolment in a higher education institution.